2009
DOI: 10.1590/s0021-75572009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação antropométrica de crianças indígenas menores de 60 meses, a partir do uso comparativo das curvas de crescimento NCHS/1977 e OMS/2005

Abstract: Conclusions:Our findings revealed important differences in the results from nutritional assessment, according to the set of growth curves used; however, the use of both growth curves revealed a high prevalence of malnutrition.Therefore, future studies with indigenous populations should present their results using two sets of growth curves to allow consistent comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
14

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 11 publications
0
9
0
14
Order By: Relevance
“…Prior to the National Survey, the great majority of available information on the nutritional status of indigenous children in Brazil came from case studies carried out over the past two decades in specific communities and local populations, most located in Amazonia [14,22,23,47-50]. These case studies found levels of stunting well above those reported for non-indigenous children (see Leite et al [51] for a review).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the National Survey, the great majority of available information on the nutritional status of indigenous children in Brazil came from case studies carried out over the past two decades in specific communities and local populations, most located in Amazonia [14,22,23,47-50]. These case studies found levels of stunting well above those reported for non-indigenous children (see Leite et al [51] for a review).…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the comprehensive influence of socioeconomic and environmental conditions on child nutrition, indigenous children in the North also present higher prevalence rates of other nutritional deficit indicators, such as anemia, and are exposed to poorer sanitation and socioeconomic conditions (e.g., access to clean drinking water and precarious living conditions) [20], which are strictly associated with chronic undernutrition. The growing body of literature on nutritional profiles of indigenous populations in the Amazon region show the frequencies of chronic undernutrition in children < 5 years of age to vary markedly from 10-20% to 50-60% in association with diverse sociocultural, economic, and environmental variables [14,22-24]. Recent diachronic studies in the Amazon demonstrate that improved socioeconomic conditions and access to sanitation and health services resulted in substantial reductions over time in the prevalence rates of chronic undernutrition among indigenous children.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Cepon-Robins et al (2013) reported that 65% of the population in this particular region is infected with parasitic worms, with even higher prevalence among children. Stunting among children is a common public health concern, and is relevant to ongoing studies investigating metabolic health in the context of economic transitioning populations (Santos & Coimbra, 2003; Foster et al, 2005; Orellana et al, 2009; Blackwell et al, 2009; Liebert et al, 2013) making nutrition-related health research a high priority in this region.…”
Section: Methodsmentioning
confidence: 99%
“…A maioria dos estudos tem autores de regiões diferentes do País [8][9][10][12][13][14][15]17,[20][21][22]28 , com vínculos com instituições das regiões Sul e Sudeste, principalmente. Apenas um estudo 28 As aldeias estudadas localizaram-se, principalmente, na região Centro-Oeste 7,9,[11][12][13][14][15]17,19,21,24,[27][28][29] ; desses estudos, quatro 9,15,19,27 cionados anteriormente, outros sete trabalhos 10,18,20,22,23,25,26 estudaram grupos localizados na região Norte. No Centro-Oeste, contemplaram--se os estados de Mato Grosso 7,9,11,12,14,15,19,24,[27][28][29] e Mato Grosso do Sul…”
Section: R E S U L T a D O Sunclassified
“…Apenas um estudo 28 As aldeias estudadas localizaram-se, principalmente, na região Centro-Oeste 7,9,[11][12][13][14][15]17,19,21,24,[27][28][29] ; desses estudos, quatro 9,15,19,27 cionados anteriormente, outros sete trabalhos 10,18,20,22,23,25,26 estudaram grupos localizados na região Norte. No Centro-Oeste, contemplaram--se os estados de Mato Grosso 7,9,11,12,14,15,19,24,[27][28][29] e Mato Grosso do Sul 13,17,21 . Na região Norte, Pará 18,19,22,25,26 , Rondônia 9,15,20,27 e Amazonas 10,…”
Section: R E S U L T a D O Sunclassified